2021
DOI: 10.1016/j.adolescence.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Can measures of sleep quality or white matter structural integrity predict level of worry or rumination in adolescents facing stressful situations? Lessons from the COVID‐19 pandemic

Abstract: Introduction COVID-19 has resulted in major life changes to the majority of the world population, particularly adolescents, with social-distancing measures such as home-based schooling likely to impact sleep quality. Increased worry is also likely considering the substantial financial, educational and health concerns accompanying COVID-19. White matter (WM) integrity has been shown to be associated with anxiety and depression symptoms, including worry, as well being closely associated with sleep q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
“…There is now gathering evidence that a number of different facets of mental wellbeing have suffered during the time of lockdowns across the globe, including but not limited to anxiety, depression, worry and rumination, stress, wellbeing and sleep [7][8][9][10][11][12][13]. For example, early on in the course of the pandemic (May 2020), initial studies in the U.S. found psychological distress levels for the previous month as high as those estimated for the previous year [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research has been conducted in general adult population above 18 years old (e. g. Boyraz et al, 2020 ; Ho et al, 2005 ; Moore & Lucas, 2020 ), while only a few studies have been carried out with particularly vulnerable populations (e.g., Maxfield & Pituch, 2020 ), healthcare workers (e.g., Puci et al, 2020 ) and people with chronically diseases (e.g., Joensen et al, 2020 ). There are some recent studies that have examined worries about COVID in adolescents (e.g., Jamieson et al, 2021 ; Lessard & Puhl, 2021 ; Vogel et al, 2021 ) and young people (e.g., Lehmann et al, 2021 ; Shukla et al, 2021 ; Yıldırım et al, 2020 ), stressing that concerns about the pandemic have a considerable impact on the negative affectivity of adolescents and young adults.…”
mentioning
confidence: 99%